Effectiveness of Non-Pharmacological Interventions in the Management of Pediatric Chronic Pain: A Systematic Review - Abel Checa-Peñalver; Cristina Lírio-Romero; Esther A. Luiz Ferreira; Sonsoles Hernandes-Iglesias; Inmaculada García-Valdivieso; Juan Manuel Pérez-Pozuelo; Sagrario Gómez-Cantarino (Children)
(1) Background: Chronic pain in children remains an under-researched area, especially compared to acute pain. This systematic review aims to evaluate the effectiveness of non-pharmacological interventions in the management of pediatric chronic pain and their impact on the well-being of both children and their families. Given the growing interest in integrative treatments to reduce reliance on pharmacological solutions, this review addresses the need for alternative therapeutic approaches. (2) Methods: A systematic review was conducted following the PRISMA guidelines, covering studies published between 2019 and 2024 from PubMed, Cochrane Library, Web of Science, and Scopus. Eligible studies included children aged 2 to 18 years with chronic pain who received non-pharmacological interventions. Data were extracted on intervention types, participant characteristics, and outcomes. The risk of bias was assessed using RoB2 for randomized trials and ROBINS-I for non-randomized studies. (3) Results: A total of 11 studies involving 1739 children were included, assessing interventions such as cognitive behavioral therapy, personalized psychosocial follow-up programs, hypnotherapy, music therapy, and digital tools. The results demonstrated significant reductions in pain severity, improvements in emotional and physical well-being, and high patient satisfaction. However, the generalizability of findings was limited by the small sample sizes and variability in study designs. (4) Conclusions: Non-pharmacological interventions appear effective in managing pediatric chronic pain, offering improvements in pain reduction and quality of life. Further research is needed to optimize these approaches and confirm their long-term benefits across diverse populations. These interventions represent promising alternatives or complements to pharmacological treatments in pediatric pain management.